Agronomic behavior of two male sterility systems in sorghum (Sorghum bicolor L. Moench). - Pecina, Víctor; Navarro, Enrique; Williams, Héctor; Rodríguez, Raúl (Agronomía Mesoamericana, 2016)
The limited genetic variability of sorghum and the use of only one type of malesterility system (Milo-Kafir, cytoplasm A1) for the production hybrid seed, make this crop susceptible to diseases, thus its importance to look for new male sterility sources, as the cytoplasm A2 reported in 1977. This systems was introduced to the elite lines of the sorghum program at the Rio Bravo Experiment Station (INIFAP-CIRNE), in Tamaulipas, Mexico. The objective of this assay was to: a) compare the agronomic traits of two male-sterility systems (A1 and A2 cytoplasms), and b) determine if there are differences of the fertility restoration in the isocytoplasmic hybrids. The experimental design was a 7 x 7 lattice with four replications. The results indicate that there are no differences among the two male-sterility systems (Al and A2 cytoplasms) in grain yield, plant height and panicIe length; whereas in days to blooming. the A2 cytoplasm was a day late than the Al cytoplasm. Different restoration responses were found in the hybrids, as the R LRB-63 line which partially restored fertility in the two types of cytoplasms, while CS-3541 showed a similar response with the LRB-l02A, LRB-104A and LRB- 1l0A lines in the A2 cytoplasm.